PELAKSANAAN PENDIDIKAN KARAKTER (RELIGIUS, CINTA TANAH AIR DAN DISIPLIN) DI SLB AL ISHLAAH PADANG - Surya Atika (Universitas Negeri Padang, 2014)
Abstract The research disaisses about the education of characters: religious, loving country and disciplin, that has been taught by teachers toward students of SLB Al Ishlaah Padang. This research has been done by observasing teacher’s strategy in teaching, process the students entering dass, studying, having a break time, going home, having extracurricular activities, etc. The results of research is the education of characters isn’t done well by the teachers because they do not apply RPP well. Actually the strategy of the teachers is good because they makes students accustomed to do good things. But unfortunatelly, they don’t evaluate the character’s development of the students. Kata Kunci:Pendidikan karakter (Religius, Cinta Tanah Air, Disilpin)